Groundwater Quality Assessment in Ambattur Industrial Estate - Sivakumar, D; Govindasami, S; Asanammal Saral, J; Arun, D; Durai Arasu, T (International Journal of Engineering and Technology, 2018)
Groundwater is generally used for various purposes, particularly domestic and industrial purposes in all over the world. Fresh water from groundwater sources is high in the recent years and the groundwater is polluted high because of rapid population and industrial growth. It is very difficult to restore the contaminated groundwater by various pollutants.  Hence, it is important to analyse physico-chemical parameters of groundwater for its need for various sectors. Therefore, the present study was under taken to define the quality of groundwater with the help of WQI. The ground water samples were collected from 20 different places around Ambattur Industrial Estate in Chennai city. The groundwater quality assessment showed that the water quality of bore wells around Ambattur Industrial Estate is poor for drinking purpose as per WQI for BIS acceptable limit.  WQI observed from those selected 20 groundwater bore wells are ranging from 63.30 to 219.63.   The analysis reveals that the groundwater from the Ambattur Industrial Estate needs pre-treatment before it is being used for various purposes.